About the subject in Spanish and Chinese languages (Philology, 2022)
The article studies the systemic regularities in the dynamic interplay between formal, semantic and pragmatic aspects of the subject in Spanish and Chinese. This approach focuses the attention on the universal and specific characteristics of the aforementioned syntactic category in typologically distinct languages, which provides an in-depth analysis of the ontology of the subject from a diachronic and synchronic point of view. The results of the empirical research are theorised from a typological perspective.
Keywords: syntactic category; subject; semantics; pragmatics; syntactic typology and universals